Strategies for Islamic Religious Education in Countering Radicalism: An Analysis of the Integration of Religious Moderation Values into the Curriculum - Hisnur Rinjani Jagat (AR-RASYID : Jurnal Pendidikan Agama Islam, 2026)
This study aims to conduct an in-depth examination of the integration of religious moderation into the development of the Islamic religious education curriculum as a means of strengthening the learner profile. This study is grounded in the urgent need to foster a moderate religious character amidst the increasingly complex dynamics of social life. In an educational context, this strengthening is of paramount importance as a preventive measure to counter the emergence of radical ideologies and intolerant attitudes that have the potential to disrupt social harmony and national values. This research employs a qualitative descriptive approach using a literature review method. Data were collected by examining various relevant literature, then analysed critically and conceptually to produce a comprehensive and structured understanding. The research subsequently found that, although the curriculum has accommodated the values of religious moderation, its implementation in practice still faces various challenges. These constraints are primarily related to the limited competence of educators, as well as the availability and quality of teaching resources. Nevertheless, the values of religious moderation can be internalised in the daily lives of students through a holistic and collaborative approach to learning. Thus, learning does not merely remain within the cognitive realm, but also touches upon behaviour and affective aspects.